Ambiguity, Iconology and Entangled Objects on Coinage of the Republican World*. (16th August 2016) - Rowan, Clare
ABSTRACT: The provincial coinage of the Roman Empire has proven to be a rich source for studying civic experiences of Roman rule, but the coins struck outside Rome during the expansion of the Roman Republic have, by contrast, received relatively little attention. This article aims to begin redressing this neglect by exploring the active rôle of coinage in conceptualizing and representing Roman Republican power. A variety of approaches to this neglected material are employed in order to highlight its potential as a source. Ambiguity, iconology, and entanglement are used as frameworks to explore case studies from across the Roman Republican world, from Spain to Syria. This approach to coin imagery under the Republic reveals the complexity and variety in which the Roman presence, and Roman imperium, was represented before the advent of the Principate.